2018
DOI: 10.1186/s40580-018-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Universal behaviour of high-Q Fano resonances in metamaterials: terahertz to near-infrared regime

Abstract: The observation of Fano resonance phenomena is universal across several branches of physics. Photonics is one of the most important areas of physics that mainly deals with the control of light propagation and localization through its interaction with natural and artificially engineered media. In an era of miniaturization, manipulation of light at micro-nanoscales has assumed unprecedented significance due to its potential to satisfy the mankind with disruptive future technologies. In this work, we present our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…The chain of dielectric disks guiding the anapole excitation was proposed by Mazzone and co-workers in [123]. It was shown that such waveguides are extremely robust against physical bending and splitting, and that the anapole state is efficiently transmitted through the S-shaped bend waveguide [141][142][143][144][145][146][147]. (c) Example of evolution of the reflectance spectrum of the metasurface from the symmetric geometry ( = 0) to a broken-symmetry geometry ( = 0.25).…”
Section: Metamaterials and Metasurfacesmentioning
confidence: 99%
“…The chain of dielectric disks guiding the anapole excitation was proposed by Mazzone and co-workers in [123]. It was shown that such waveguides are extremely robust against physical bending and splitting, and that the anapole state is efficiently transmitted through the S-shaped bend waveguide [141][142][143][144][145][146][147]. (c) Example of evolution of the reflectance spectrum of the metasurface from the symmetric geometry ( = 0) to a broken-symmetry geometry ( = 0.25).…”
Section: Metamaterials and Metasurfacesmentioning
confidence: 99%
“…Top: Schematic of light scattering by a metasurface. Bottom: Designs of unit cells of metasurfaces with a broken in-plane inversion symmetry of constituting meta-atoms supporting sharp resonances, analysed in Refs [4][5][6][7][8][9][10][11][12][13]…”
mentioning
confidence: 99%
“…That fact limits the implementation of such devices in several applications like precise sensing. The narrow linewidth and high Q-factor in the transmission spectrum of the metamaterial can be achieved by incorporating Fano resonances, originating from the coherent coupling (interference) between discrete and continuous states [12,13]. These resonances show a sharp and asymmetric spectral line shape and produce a large strength and localization of the electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%